Teaching chess tactics with SWOT and Stephen Covey matrices: Effects on tactical behavior and cognition - Najm, Mohammed Suhail (Tanjungpura Journal of Coaching Research, 2026)
Background The growing need to develop students’ strategic thinking, self-management, and decision-making skills has become a top educational priority. This challenge underscores the necessity of implementing innovative educational approaches that integrate cognitive and tactical training. Objectives The research aims to develop two educational programs based on the SWOT matrix and Stephen Covey’s matrix. Also, it aims to reveal the impact of these programs on tactical behavior and the development of certain mental abilities. Methods The experimental method was used due to its suitability and the nature of the research. The research population represents outstanding first-year middle school students in the city of Mosul. The study sample was divided into three divisions. Division A was a control group; Division B was the first experimental group, which was studied using the SWOT matrix; Division C was the second experimental group and was studied according to the Stephen Covey matrix. The data were statistically analyzed using SPSS 26. Results The results show that students taught using the SWOT matrix achieved significantly higher scores than students taught using Stephen Covey’s matrix and conventional methods.The first experimental group outperformed both groups across all spatial ability tests (LSD = 13.80, 9.05, 9.62, and 32.47), compared with the second experimental group (LSD = 11.85, 6.97, 7.27, and 26.08) and the control group (LSD = 9.07, 5.47, 6.55, and 21.08). Furthermore, the first experimental group demonstrated superior performance across all levels of the tactical behavior test. Conclusion Teaching chess tactics through structured strategic frameworks, particularly the SWOT matrix, significantly enhances students’ tactical behavior, attention, and spatial ability compared with both Stephen Covey’s matrix and traditional instruction. This study contributes to the literature by demonstrating the effectiveness of integrating educational planning and decision-making models into chess instruction.